Mitral endocarditis caused by Achromobacter xylosoxidans in an older patient: Case report and literature review. (2022) - Kengni Tameze, Joseph; Korpak, Kéziah; Compagnie, Michèle; Levie, Henrianne; Cherifi, Soraya; Lali, Salah Eddine
Abstract: We report a rare case of recurrent Achromobacter xylosoxidans bacteremia in an older woman in 2014 and 2020. During the more recent bacteremia, a diagnosis of mitral endocarditis was made. The patient could not have surgery because of severe comorbidities and a high operative risk. Combined antibiotic therapy was given with piperacillin/tazobactam and trimethoprim/sulfamethoxazole (TMP/SMX). Antibiotic therapy was administered for six weeks with a good response, but the patient relapsed after six days with A. xylosoxidans bacteremia and cardiac decompensation. Antibiotic therapy was resumed, using meropenem and TMP/SMX, but the patient died one month after the recurrence. We review the 22 cases of A. xylosoxidans endocarditis that have been described in the literature.